Performance and Fuel Consumption Optimizations of Shunting Hybrid Locomotives - Matej Pacha; Jiri Stepanek (Communications - Scientific letters of the University of Zilina, 2013)
In recent years hybrid electric drive has become very popular in public transportation and automobiles. This article deals with hybrid drive technology and its impact on performance and energy consumption optimization of shunting locomotives in comparison with conventional diesel-electric locomotives. Based on classic longitudinal train dynamics theory of train movement and with support of simulation results, a comparison of electrochemical accumulators and super-capacitors impact is also introduced.